2022
DOI: 10.1177/20417314211073934
|View full text |Cite
|
Sign up to set email alerts
|

Precision-engineered niche for directed differentiation of MSCs to lineage-restricted mineralized tissues

Abstract: The major difference between tissue healing and regeneration is the extent of instructional cues available to precisely direct the biological response. A classic example is reparative or osteodentin that is seen in response to physicochemical injury to the pulp-dentin complex. Dentin regeneration can direct the differentiation of dental stem cells using concerted actions of both soluble (biomolecules, agonists, and antagonists) and insoluble (matrix topology) cues. The major purpose of this study was to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Dental pulp stem cells can differentiate into odontoblast-like cells, forming secondary or reparative dentin. (Chen et al, 2021;Rahman et al, 2022). Exploring the function of the pulp-dentin complex facilitates comprehensive identification of the underlying mechanism of dental abnormalities in CCD.…”
Section: Discussionmentioning
confidence: 99%
“…Dental pulp stem cells can differentiate into odontoblast-like cells, forming secondary or reparative dentin. (Chen et al, 2021;Rahman et al, 2022). Exploring the function of the pulp-dentin complex facilitates comprehensive identification of the underlying mechanism of dental abnormalities in CCD.…”
Section: Discussionmentioning
confidence: 99%
“…Non parametric tests was used for the analysis between the groups and independent groups comparison Mann Whitney U test was used. 21 The representative results are presented as the Mean ± Standard deviation (SD) where p value equal or <0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…These molecules can be incorporated into nanofibrous scaffolds for sustained and controlled drug delivery. 21 Therefore, we investigated the release of TG from the nanofibers and demonstrated a constant release from the nanofibers up to 7 days. The relative release profile of TG from PCLF-TG100 nanofibers showed that during 1 h, 1.69% w/v of incorporated TG was released (Table 2).…”
Section: Release Of Tg From Nanofibers Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“… 48 Therefore, innovative approaches through therapeutic delivery vehicles and nanostructures were designed to preserve miRNAs and offer gene expression modulatory therapies for various biomedical applications. 48 50 Rahman et al 51 suggest that the application of biomaterial nanopatterning and controlled-release morphogens could enhance MSC differentiation towards an osteogenic bias. Hence, ‘training’ MSCs towards a specific functional identity, improving their intramural achievements or strengthening the MSC transplantation protocols have become imperative.…”
Section: The Operational Agenda Of Mscsmentioning
confidence: 99%